Pembelajaran Seni Rupa Untuk Anak Berkebutuhan Khusus Jenjang SMA Di SLB Perwari Ulak karang - DIDI SUSANTO,n Drs. Wisdiarman, M.Pd. (Serupa The Journal of Art Education, 2019)
The purpose of this research is to analyze the study of Arts for Autism in Senior High School of SLB Perwari Ulak Karang Padang. This research used descriptive method, located in SLB Perwari Ulak Karang Padang. The method used for collecting the data is observing, documenting and interviewing, The object of the research is the teachers and the headmaster of SLB Perwari. The result of the study is The Arts is begun with preparing the lesson plan toward the programs based on the students needed and The application used is thematic method.Keyword: Extraordinary School, (SLB), Autism (ABK). Arts. The subject